Dimethyl Sulfoxide Attenuates Hydrogen Peroxide‐Induced Injury in Cardiomyocytes via Heme Oxygenase‐1. Issue 6 (June 2014) - Man, Wang; Ming, Ding; Fang, Du; Chao, Liang; Jing, Cang
ABSTRACT The antioxidant property of dimethyl sulfoxide (DMSO) was formerly attributed to its direct effects. Our former study showed that DMSO is able to induce heme oxygenase‐1 (HO‐1) expression in endothelial cells, which is a potent antioxidant enzyme. In this study, we hypothesized that the antioxidant effects of DMSO in cardiomyocytes are mediated or partially mediated by increased HO‐1 expression. Therefore, we investigated whether DMSO exerts protective effects against H2O2‐induced oxidative damage in cardiomyocytes, and whether HO‐1 is involved in DMSO‐imparted protective effects, and we also explore the underlying mechanism of DMSO‐induced HO‐1 expression. Our study demonstrated that DMSO pretreatment showed a cytoprotective effect against H2O2‐induced oxidative damage (impaired cell viability, increased apopototic cells rate and caspase‐3 level, and increased release of LDH and CK) and this process is partially mediated by HO‐1 upregulation. Furthermore, our data showed that the activation of p38 MAPK and Nrf2 translocation are involved in the HO‐1 upregulation induced by DMSO. This study reports for the first time that the cytoprotective effect of DMSO in cardiomyocytes is partially mediated by HO‐1, which may further explain the mechanisms by which DMSO exerts cardioprotection on H2O2 injury. J. Cell. Biochem. 115: 1159–1165, 2014. © 2013 Wiley Periodicals, Inc.